Red blood cell distribution width is not a reliable biomarker for low iron stores in children with cystic fibrosis. (2nd January 2017) - Akkermans, M. D.; Uijterschout, L.; Nuijsink, M.; Hendriks, D. M.; van Goudoever, J. B.; Brus, F.
ABSTRACT: Low iron stores in children, absolute iron deficiency (AID), can lead to impaired neurodevelopment and requires iron therapy. In the presence of infection/inflammation, like in cystic fibrosis (CF), serum ferritin (SF) is not a reliable biomarker for AID. Red blood cell distribution width (RDW) is a promising alternative reported not to be influenced by infection in healthy children. Currently, there are no data on the diagnostic capacity of RDW to detect AID in pediatric CF patients. This was a prospective observational study that investigated iron status biomarkers in 53 Dutch pediatric CF patients. AID was defined using World Health Organization criteria for SF in stable patients (no recent pulmonary exacerbation) and C-reactive protein (CRP) ≤10 mg/l. Patients with AID had higher RDW levels than patients without AID ( p = 0.019). An RDW ≥13.2% showed the following test statistics: sensitivity 100%; specificity 39.4%; positive predictive value 20%; and negative predictive value 100%. Furthermore, we found a correlation between RDW and CRP in the total group that originated from the stable patients (r = 0.308; p = 0.042). In conclusion, the diagnostic capacity of RDW for detecting AID in pediatric CF patients seems limited because RDW levels might also be influenced by chronic infection/inflammation in these patients.